1982
DOI: 10.1002/food.19820261014
|View full text |Cite
|
Sign up to set email alerts
|

Fortschrittsbericht Die intestinale Phase der Peptidabsorption

Abstract: Peptides and not amino acids are the prevailing degradation products of protein digestion which are formed in the intestinal lumen and are absorbed from the mucosa. These two families differ in absorption. The differences become manifest when the absorption of peptide mixtures is compared with that of equimolecular mixtures of free amino acids. The absorption of peptides occurs in two different ways: 1. Transport of intact peptides through the membrane into the mucosal cell and subsequent hydrolysis by intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Proteinhydrolysates are characterized by a rapid intestinal absorption of amino acids (7) resulting in elevated plasma concentrations of amino acids postprandially (20). We have shown that elevated amino acids concentrations in serum can aggravate the physiologie cholestasis of newborns in VLBW-infants (18).…”
Section: Introductionmentioning
confidence: 99%
“…Proteinhydrolysates are characterized by a rapid intestinal absorption of amino acids (7) resulting in elevated plasma concentrations of amino acids postprandially (20). We have shown that elevated amino acids concentrations in serum can aggravate the physiologie cholestasis of newborns in VLBW-infants (18).…”
Section: Introductionmentioning
confidence: 99%